Oil Spill Cleanup Employing Surface Modified Magnetite Nanoparticles Using Two New Polyamines - Mahmood M. S. Abdullah; Mohd Sajid Ali; Hamad A. Al-Lohedan (Journal of Chemistry)
Oil spills in marine environments are a serious environmental concern and using low-cost materials for oil spill cleanup is an emerging subject. In recent years, surface-modified magnetite nanoparticles (MNPs) have shown promising properties for oil spill cleanup due to their high performance, low cost, magnetic properties, and reusability. This study aims to modify the surface of magnetite nanoparticles (MNPs) using two new polyamines and employ them for oil spill remediation. First, tetraethylene glycol (TEG) was converted to the corresponding alkyl halide (AH). Next, two polyamines were synthesized via the alkylation of diamines, 1,11-undecanediamine (UD) and 1,5-pentanediamine (PD), yielding the corresponding AH-UD and AH-PD polyamines. Finally, AH-UD and AH-PD were applied to MNPs’ surface modification, yielding the corresponding surface-modified MNPs, AU-MNPs, and AP-MNPs. The performance of AU-MNPs and AP-MNPs for oil spill uptake (OSU%) was investigated using various MNPs-to-oil ratios at different contact times. Furthermore, the reusability of AU-MNPs and AP-MNPs was also investigated over four cycles. The results indicated that the OSU values of AU-MNPs and AP-MNPs were affected by MNPs’ ratios and contact time, where their OSU increased as their ratios and contact time increased. In addition, AU-MNPs showed a higher OSU than AP-MNPs, which could be ascribed to the longer alkyl chain in the polyamine (AH-UA) used for their surface modification compared to AP-MNPs. Furthermore, AU-MNPs and AP-MNPs reusability results exhibited effective OSU in four cycles with a relative decline with an increasing number of cycles.